EFEKTIVITAS TEKNIK STRETCHING DALAM MENGURANGI NYERI PUNGGUNG BAWAH PADA INDIVIDU YANG BEROLAHRAGA SECARA RUTIN - Yunita, Alfitri Yana; Yanti, Dewi Sepi (LPPM Universitas Awal Bros, 2024)
Lower back pain is one of the most common musculoskeletal issues experienced by individuals who exercise regularly. One method that can be used to reduce this pain is stretching techniques. This study aims to analyze the effectiveness of stretching techniques in reducing lower back pain in individuals who engage in regular physical exercise. The research method used was an experimental design with a pre-test and post-test approach applied to the intervention group. The study sample consisted of individuals who exercised regularly and experienced lower back pain, who were then given an intervention in the form of stretching techniques for a specific period. Pain levels were measured using the Visual Analog Scale (VAS) before and after the intervention. The results of the study showed a significant reduction in lower back pain levels after the stretching intervention (p < 0.05). This indicates that stretching techniques are effective in reducing lower back pain in individuals who exercise regularly. Therefore, stretching techniques can be recommended as one of the preventive and management strategies for lower back pain among physically active individuals.